Supporting transitions in medical career pathways: the role of simulation-based education. Issue 1 (January 2016) - Cleland, Jennifer; Patey, Rona; Thomas, Ian; Walker, Kenneth; O'Connor, Paul; Russ, Stephanie
Abstract Transitions, or periods of change, in medical career pathways can be challenging episodes, requiring the transitioning clinician to take on new roles and responsibilities, adapt to new cultural dynamics, change behaviour patterns, and successfully manage uncertainty. These intensive learning periods present risks to patient safety. Simulation-based education (SBE) is a pedagogic approach that allows clinicians to practise their technical and non-technical skills in a safe environment to increase preparedness for practice. In this commentary, we present the potential uses, strengths, and limitations of SBE for supporting transitions across medical career pathways, discussing educational utility, outcome and process evaluation, and cost and value, and introduce a new perspective on considering the gains from SBE. We provide case-study examples of the application of SBE to illustrate these points and stimulate discussion.